2009
DOI: 10.1007/s12032-009-9294-9
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide induces apoptosis in NB-4, an acute promyelocytic leukemia cell line, through up-regulation of p73 via suppression of nuclear factor kappa B-mediated inhibition of p73 transcription and prevention of NF-κB-mediated induction of XIAP, cIAP2, BCL-XL and survivin

Abstract: The purpose of the present study is to evaluate the effects of arsenic trioxide (ATO) on human acute promyelocytic leukemia NB-4 cells. Microculture tetrazolium test, bromodeoxyuridine (BrdU) cell proliferation assay, caspase 3 activity assay, cell-based nuclear factor kappa B (NF-kappaB) phosphorylation measurement by ELISA and real-time RT-PCR were employed to appraise the effects of ATO on metabolic activity, DNA synthesis, induction of programmed cell death and NF-kappaB activation. The suppressive effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…C35 and ΔNp73 colocalize at peri-nuclear region, suggesting a transcriptional-independent mechanism of NFκB and AKT activation. EGCG (epigallocatechin-3-gallate ) Upregulation of TAp73 expression [187][188][189] Red wine polyphenol Upregulation of TAp73 expression 190 Arsenic trioxide Upregulation of TAp73 expression 191,192 T-oligo Oligonucleotides homologous to the 3′-telomere overhang; upregulation of TAp73 expression 167,193,194 Propranolol Nonselective β-adrenergic receptor antagonist; upregulation of TAp73 expression 195 Melphalan Upregulation of TAp73 expression 196 Sodium butyrate Histone deacetylase inhibitor; upregulation of TAp73 expression 197 7-hydroxy-staurosporine Upregulation of TAp73 expression 197 Hydroxyurea DNA replication inhibitor; upregulation of TAp73 expression 198 Aphidicolin DNA polymerase α inhibitor; upregulation of TAp73 expression 198 Resveratrol DNA replication inhibitor; upregulation of TAp73 expression 198 4-propoxyphenol DNA replication inhibitor; upregulation of TAp73 expression 198 Celecoxib COX-2 inhibitor; upregulation of TAp73 and reduction of DNp73 expression 9,199 Tazarotene Upregulation of TAp73 and reduction of DNp73 expression 200 Interferon (IFN)α Reduction of DNp73 expression 201 …”
Section: Dna Damage Suppresses Dnp73mentioning
confidence: 99%
“…C35 and ΔNp73 colocalize at peri-nuclear region, suggesting a transcriptional-independent mechanism of NFκB and AKT activation. EGCG (epigallocatechin-3-gallate ) Upregulation of TAp73 expression [187][188][189] Red wine polyphenol Upregulation of TAp73 expression 190 Arsenic trioxide Upregulation of TAp73 expression 191,192 T-oligo Oligonucleotides homologous to the 3′-telomere overhang; upregulation of TAp73 expression 167,193,194 Propranolol Nonselective β-adrenergic receptor antagonist; upregulation of TAp73 expression 195 Melphalan Upregulation of TAp73 expression 196 Sodium butyrate Histone deacetylase inhibitor; upregulation of TAp73 expression 197 7-hydroxy-staurosporine Upregulation of TAp73 expression 197 Hydroxyurea DNA replication inhibitor; upregulation of TAp73 expression 198 Aphidicolin DNA polymerase α inhibitor; upregulation of TAp73 expression 198 Resveratrol DNA replication inhibitor; upregulation of TAp73 expression 198 4-propoxyphenol DNA replication inhibitor; upregulation of TAp73 expression 198 Celecoxib COX-2 inhibitor; upregulation of TAp73 and reduction of DNp73 expression 9,199 Tazarotene Upregulation of TAp73 and reduction of DNp73 expression 200 Interferon (IFN)α Reduction of DNp73 expression 201 …”
Section: Dna Damage Suppresses Dnp73mentioning
confidence: 99%
“…Cell cytotoxicity was determined using MTT assay, as previously reported [20]. Briefly, the cells (5,000/well) were plated in 96-well plates and incubated at 37°C; the metabolic activity was assessed after 48 h by an uptake of thiazolyl blue tetrazolium bromide (Sigma) by viable cells at 490 nm.…”
Section: Cell Line and Ato Treatmentmentioning
confidence: 99%
“…After exposed to substrate tetramethyl-benzidine, the samples were read at 450 nm in an ELISA reader. The inhibitory rate of ATO on the proliferation of NB4 cells was calculated as previously described [20].…”
Section: Brdu Cell Proliferation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the transcription factor NF-κB is a key pro-survival mechanism in cancer cells [36] and studies have shown that cIAP2 is a target gene of NF-κB [37,38]. Therefore, we examined whether NF-κB activation is involved in the pro-survival effect of Gli1 as well as up-regulation of cIAP2 expression.…”
Section: Nf-κb/ciap2 Signaling Partially Contributes To the Pro-survimentioning
confidence: 99%